La experimentación como estrategia didáctica para el aprendizaje de química orgánica en tercer año de bachillerato intensivo de la unidad educativa “Camilo Gallegos Domínguez - Villa Chafla, Saraí Patricia (2023)
ABSTRACT: At present, the learning of Organic Chemistry is considered a challenge for the educator, therefore the use of striking didactic strategies such as experimentation is recommended. The research problem is based on: How does experimentation as a didactic strategy contribute to learning Organic Chemistry? The objective was: "Propose experimentation as a didactic strategy for learning Organic Chemistry". The methodology was based on a quantitative approach with a pre-experimental and systematic design, the type of research was documentary; designing a methodological guide on the use of experimentation in Organic Chemistry, whose level was descriptive, explanatory and laboratory. For the data collection, the survey consisting of 10 strategic questions was used in order to analyze the level of acceptance of the use of the methodological guide and the written evaluations with the application of the test-retest for the analysis of the learning scope in the subject. The population consisted of 75 students from the "Camilo Gallegos Domínguez" Educational Unit, from which a sample of 25 students selected by probabilistic-intentional test was obtained. The results reflected that all the students agree that it is important to apply experimentation as a didactic strategy for learning. It was concluded that the experimentation complements the teaching-learning process of Organic Chemistry because it converts the theoretical and extensive contents into applied activities related to daily living. Therefore, it is recommended to promote the use of the methodological guide as an enhancer of significant learning in the subject. Keywords: Learning, Didactic Strategy, Experimentation, Organic Chemistry.